Prognostic subtyping based on estrogen receptor, progesterone receptor, and human epidermal growth factor receptor2 expression in breast cancer cases among north Indian females - Lone, Kouser Sideeq; Parveena, Shaheena (International Journal Of Community Medicine And Public Health, 2018)
Background: Cancer of breast has recently become the leading cancer among women in Kashmir. Worse prognosis of this disease is with the features of higher grade, positivity for Her-2/neu, negativity for ER, PR, and presence of BRCA gene. Thus the receptor status like are a very useful tool for rapid diagnosis, treatment as well as for prognosis of the disease. The objective of the study was to analyze the pattern of expression of hormone receptors which include ER, PR and Her-2/neu in breast cancer cases among Kashmiri females and to find their association with various clinicopathological parameters. Methods: A cross sectional hospital based study done in a tertiary health care centre of Kashmir valley. We selected 102 consecutive breast cancer cases for the period of one year. Cases were sent for biopsy of the tumour lesion and for receptor status analysis. Results: In about 50.9%of cases tumour had spread to T2 stage. There was a significant difference in the tumor stage and the age groups at presentation. The HER 2 status was positive in 85.5% of cases. About 65% were ER positive and 51.9 were PR positive. Only 8 were triple negative and 42 were triple positive for receptors. We did not found any significant relationship between grade, stage of disease and age when compared for receptor status. Conclusions: We found a high percentage being receptor positive tumours which has been found to be a good prognostic sign.